Modellbildung, Parameteridentifikation und Regelung hoch ausgenutzter Synchronmaschinen - Richter, Jan (KIT Scientific Publishing, 2016)
What happens when permanent-magnet electric motors with identical power become smaller and lighter? How changes the electromagnetic behavior? What consequences arise with respect to optimal motor control? This study answers these questions and discusses modeling, parameter identification, and control over inverter-fed, magnetically anisotropic, highly utilized, permanent-magnet synchronous motors.